The Broken Bridge of Collaboration: Unpacking Poverty Politics in Eastern Indonesia - Onga, Fiko; Handoko, V. Rudy; Maduwinarti, Ayun (Kirana Publisher (KNPub), 2025)
This study investigates the implementation of Collaborative Governance in poverty alleviation programs in Bolaang Mongondow Timur Regency, North Sulawesi. Grounded in a constructivist paradigm, the research adopts a qualitative case study approach. Data were collected through in-depth interviews, observations, document analysis, and focus group discussions involving stakeholders from five key sectors: government, business, academia, civil society, and media. The findings reveal that although a formal structure (TKPKD) has been established to facilitate coordination, its effectiveness has been compromised following the issuance of Presidential Regulation No. 163/2024, which dissolved the existing institutional framework without providing operational guidelines for its replacement (BPPK). The study identifies a paradox of collaboration: formal documents and coordination mechanisms exist, yet genuine multi-actor interaction remains limited. The involvement of non-government actors is mainly instrumental and symbolic, with civil society and media often excluded from meaningful deliberation. The research concludes that Collaborative Governance in the region remains characterized by a top-down administrative logic rather than an inclusive, transformative practice. A key recommendation is the institutionalization of regular, deliberative, and open multi-actor forums supported by accurate and transparent data systems. This study contributes theoretically by offering a localized adaptation of the Pentahelix model, enriched by institutional improvisation and contextual wisdom.